Hemopoiesis stimulating and radioprotective effects of carboxymethylglucan - Pospísil, M; Sandula, J; Pipalová, I; Hofer, M; Viklická, S (Physiological research, 1991)
Carboxymethylglucan, a novel soluble derivative of beta-1,3-glucan, was found to enhance hemopoietic recovery in sublethally gamma-irradiated mice and to increase survival in lethally irradiated animals when given 24 hours prior to irradiation. Postirradiation treatment with carboxymethylglucan also induced favourable effects in terms of survival when used in combination with preirradiation cystamine administration.
Keywords: Male; Mice, Inbred CBA; Dextrans; Hematopoiesis; Mice; dextrany; myši inbrední C57BL; Gamma Rays; myši inbrední CBA; záření gama; hematopoéza; mužské pohlaví; radioprotektivní látky; Animals; Mice, Inbred C57BL; zvířata; Radiation-Protective Agents; myši